Reconstructing the Evidentiary Framework for Corruption Offenses to Strengthen Legal Certainty - Dany Try Hutama Hutabarat; Adi Mansar; Surya Perdana (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Corruption remains one of the most challenging crimes to prosecute because its complex nature frequently exceeds the capacity of conventional evidentiary mechanisms. This study examines the reconstruction of the evidentiary framework for corruption offenses in Indonesia to strengthen legal certainty while maintaining due process and the protection of defendants' rights. A normative legal research design was employed using statutory, conceptual, comparative, and case approaches. Primary and secondary legal materials, including legislation, judicial decisions, and legal doctrines, were analyzed through qualitative legal interpretation. The findings reveal that the existing evidentiary framework remains fragmented across the Criminal Procedure Code, the Corruption Eradication Law, and other related regulations, resulting in inconsistencies regarding electronic evidence, scientific evidence, audit reports on state financial losses, and the implementation of the limited reverse burden of proof. To address these deficiencies, this study proposes an integrated evidentiary framework that harmonizes conventional and digital evidence, strengthens standards for scientific and audit evidence, improves evidence monitoring mechanisms, and reconstructs Article 37 of the Corruption Eradication Law by introducing an oath requirement within a constitutionally limited reverse burden of proof. This reconstruction provides a coherent legal framework that enhances judicial consistency, improves evidentiary reliability, and reinforces legal certainty in corruption adjudication while remaining consistent with fundamental principles of criminal justice and human rights.